Rancang Bangun Sistem Jemuran Otomatis dan Monitoring Cuaca berbasis Logika Fuzzy - Sasongko, Alexander Ardian Pulung; Nurraharjo, Eddy (STMIK Banjarbaru, 2026)
Weather uncertainty in tropical regions often hinders the drying process and increases the risk of clothes getting wet again due to rain. This study aims to design a smart clothesline system based on the Internet of Things (IoT) with monitoring and adaptive automation capabilities. The methodology applied is prototyping using an ESP32 microcontroller integrated with BME280, BH1750, YL-83, and clothing dryness sensors, as well as utilizing Fuzzy Logic for decision making on the position of the drying rack poles. The main findings show that the environmental sensors have high accuracy with an average error of less than 1%. The Fuzzy algorithm proved effective in executing safety priorities by retracting the drying rack during rain, as well as improving efficiency by automatically retracting the drying rack when clothes are detected as dry by the sensor. It is concluded that this system successfully provides a reliable and efficient autonomous solution for drying management amid dynamic weather conditions.Keywords: Automatic Clothesline; ESP32; Fuzzy Logic; Internet of Things; Weather Monitoring. AbstrakKetidakpastian cuaca di wilayah tropis sering menghambat proses pengeringan dan meningkatkan risiko pakaian basah kembali akibat hujan. Penelitian ini bertujuan merancang sistem jemuran cerdas berbasis Internet of Things (IoT) dengan kemampuan monitoring dan otomasi adaptif. Metodologi yang diterapkan adalah prototyping menggunakan mikrokontroler ESP32 yang terintegrasi dengan sensor BME280, BH1750, YL-83, dan sensor kekeringan pakaian, serta memanfaatkan Logika Fuzzy untuk pengambilan keputusan posisi tiang jemuran. Temuan utama menunjukkan bahwa sensor lingkungan memiliki akurasi tinggi dengan rata-rata error di bawah 1%. Algoritma Fuzzy terbukti efektif menjalankan prioritas keamanan dengan menarik tiang jemuran saat hujan, serta meningkatkan efisiensi dengan menarik jemuran secara otomatis saat pakaian terdeteksi kering oleh sensor. Disimpulkan bahwa sistem ini berhasil memberikan solusi otonom yang andal dan efisien untuk manajemen penjemuran di tengah kondisi cuaca dinamis.